Observations of winter storms with a video disdrometer and polarimetric radar - Ikeda, Kyoko, author; Department of Atmospheric Science, Colorado State University, publisher (Colorado State University. Libraries, 2007)
With efforts to upgrade the operational NEXRAD radars to include polarimetric capability underway, there are growing interests in developing radar-based algorithms for classifying hydrometeor types, quantifying winter precipitation, and improving the parameterization of winter precipitation in numerical forecast models. The capabilities of polarimetric radars, such as to better quantify warm season precipitation, have been demonstrated in various studies. However, these tasks are further complicated for winter precipitation by the need to know hydrometeor phase and bulk density of ice particles. In this study, data collected with a two-dimensional video disdrometer and S-band dual polarization radar during the Winter Icing and Storms Project 2004 (WISP04) storms are examined in support of ongoing research to develop radar-based algorithms for cold season precipitation. The capability to match radar-measured and disdrometer-based calculations of radar reflectivity factor and differential reflectivity is essential for retrieving hydrometeor characteristics with radar. During the WISP04, the disdrometer provided detailed information regarding hydrometeor size, number concentration, terminal velocity, and shape during the precipitation events. In this study, bulk ice particle density is estimated using an empirical relationship derived from disdrometer measurements of precipitation volume and rain gauge measurements of precipitation mass. Reflectivity and differential reflectivity, as measured by radar and computed from disdrometer observations are compared, and the combined dataset is used to examine storm microphysical properties. The measurements and computed values show good agreement and reveal that the radar detected subtle changes in the characteristics of winter precipitation. Additionally, sensitivity of the scattering computations to assumed ice particle characteristics is examined, and particle size distributions from radar measurements are retrieved for comparisons with the disdrometer observations.
Spring 2007.
Keywords: Winter storms; Radar meteorology